2018
DOI: 10.3390/microorganisms6020035
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Power of Microbiome Assessment Tools as Part of Neuroprotective Nutrition and Lifestyle Medicine Interventions

Abstract: An extensive body of evidence documents the importance of the gut microbiome both in health and in a variety of human diseases. Cell and animal studies describing this relationship abound, whilst clinical studies exploring the associations between changes in gut microbiota and the corresponding metabolites with neurodegeneration in the human brain have only begun to emerge more recently. Further, the findings of such studies are often difficult to translate into simple clinical applications that result in meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 258 publications
(255 reference statements)
0
20
0
3
Order By: Relevance
“…Pre-clinical models have also demonstrated a relationship between gastrointestinal dysfunction and autism spectrum disorders, with a focus on the role of the BGA [ 75 ]. In addition, several clinical studies have examined the relationship between the gut microbiome and brain activity [ 76 ]. Pinto-Sanchez et al studied patients suffering from irritable bowel syndrome (IBS) and discovered that a probiotic treatment effectively reduced depression and improved quality of life in IBS patients [ 77 ].…”
Section: Brain-gut Axis and Neurologic Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-clinical models have also demonstrated a relationship between gastrointestinal dysfunction and autism spectrum disorders, with a focus on the role of the BGA [ 75 ]. In addition, several clinical studies have examined the relationship between the gut microbiome and brain activity [ 76 ]. Pinto-Sanchez et al studied patients suffering from irritable bowel syndrome (IBS) and discovered that a probiotic treatment effectively reduced depression and improved quality of life in IBS patients [ 77 ].…”
Section: Brain-gut Axis and Neurologic Injurymentioning
confidence: 99%
“…While zonulin, a crucial protein in regulation of intestinal permeability, has not yet been widely explored as a treatment target for traumatic brain injury, one research team found that zonulin was involved in several diseases of autoimmune, neurodegenerative, and tumoral nature, and could function as an indicator of gut barrier damage in these conditions as well as a potential therapeutic target [ 98 ]. A recent review also discussed potential measures to reduce levels of zonulin and subsequently improve intestinal permeability [ 76 ]. This review cited a clinical study done in Austria that analyzed the effects of zeolite supplementation in endurance-trained individuals and found that this intervention correlated with decreased levels of excreted zonulin as well as decreased inflammation [ 76 , 99 ].…”
Section: Potential Therapeutic Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review, Pruimboom and Muskiet [38] discussed the disparity between the plant diversity of Homo sapiens' diet of over 135,00 years ago at over 3000 species compared to the modern-day diet of which 400 plant species are gathered, but only more than 100 are utilized for food. Research suggests that greater variety of fruits and vegetables may have more significant impact on health markers like blood pressure, oxidative damage, and risk of falls than a less-varied diet [39][40][41][42]. In an excellent review article making a case for food diversity for the gut microbiome, Toribio-Mateas [43] recommends a "50-food challenge" chart to log intake of fresh fruits, vegetables, herbs, and spices over a 7-day period.…”
Section: Botanical Diversity and Colormentioning
confidence: 99%
“…Research suggests that greater variety of fruits and vegetables may have more significant impact on health markers like blood pressure, oxidative damage, and risk of falls than a less-varied diet [39][40][41][42]. In an excellent review article making a case for food diversity for the gut microbiome, Toribio-Mateas [43] recommends a "50-food challenge" chart to log intake of fresh fruits, vegetables, herbs, and spices over a 7-day period. e intended goal is to help individuals track their eating pattern for the benefit of providing a wide range of prebiotic compounds, especially polyphenols [44], from plant-based foods to feed a vast spectrum of bacteria.…”
Section: Botanical Diversity and Colormentioning
confidence: 99%